Comparative Antiviral Activity of Remdesivir and Anti-HIV Nucleoside Analogs against Human Coronavirus 229E (HCoV-229E) - Keykavous Parang; Naglaa Salem El-Sayed; Assad J. Kazeminy; Rakesh K. Tiwari (Molecules, 2020)
Remdesivir is a nucleotide prodrug that is currently undergoing extensive clinical trials for the treatment of COVID-19. The prodrug is metabolized to its active triphosphate form and interferes with the action of RNA-dependent RNA polymerase of SARS-COV-2. Herein, we report the antiviral activity of remdesivir against human coronavirus 229E (HCoV-229E) compared to known anti-HIV agents. These agents included tenofovir (TFV), 4′-ethynyl-2-fluoro-2′-deoxyadenosine (EFdA), alovudine (FLT), lamivudine (3TC), and emtricitabine (FTC), known as nucleoside reverse-transcriptase inhibitors (NRTIs), and a number of 5′-O-fatty acylated anti-HIV nucleoside conjugates. The anti-HIV nucleosides interfere with HIV RNA-dependent DNA polymerase and/or act as chain terminators. Normal human fibroblast lung cells (MRC-5) were used to determine the cytotoxicity of the compounds. The study revealed that remdesivir exhibited an EC50 value of 0.07 µM against HCoV-229E with TC50 of > 2.00 µM against MRC-5 cells. Parent NRTIs were found to be inactive against (HCoV-229E) at tested concentrations. Among all the NRTIs and 5′-O-fatty acyl conjugates of NRTIs, 5′-O-tetradecanoyl ester conjugate of FTC showed modest activity with EC50 and TC50 values of 72.8 µM and 87.5 µM, respectively. These data can be used for the design of potential compounds against other coronaviruses.